CD8 lymphocytes in tumors and nonsynonymous mutational load correlate with prognosis of bladder cancer patients treated with immune checkpoint inhibitors. Issue 1 (10th April 2018) - Deng, Boya; Park, Jae‐Hyun; Ren, Lili; Yew, Poh Yin; Kiyotani, Kazuma; Antic, Tatjana; O'Connor, Kelly; O'Donnell, Peter H.; Nakamura, Yusuke
Abstract: Background: Anti–programed cell death 1 checkpoint inhibitors have recently demonstrated effectiveness against metastatic cancers including urothelial carcinoma. Aims: To identify biomarkers/factors that correlate with the clinical response in advanced bladder cancer patients who received immune checkpoint inhibitor treatment. Methods and results: We investigated tumors from 18 bladder cancer patients who had received anti–programed cell death 1 (pembrolizumab) or anti–programmed death‐ligand 1 therapy (atezolizumab or durvalumab) and performed exome analysis, T‐cell receptor sequencing of the tumor‐infiltrating lymphocytes (TILs), and immunohistochemical analysis of CD8 and programmed death‐ligand 1 in cancer tissues. Immunohistochemical analysis of bladder cancer tissues demonstrated that a higher number of CD8 T‐cell infiltration into cancer tissues was significantly associated with longer cancer‐specific survival of the patients ( P = .0012). T‐cell receptor beta sequencing of TILs using genomic DNAs extracted from the tissues of 15 cases revealed that patients with higher clonal expansion of TILs had some tendency of longer cancer‐specific survival ( P = .055), than those with lower clonal expansion. We performed whole exome sequencing of 14 cases and found that patients carrying higher numbers of somatic mutations received greater benefit from immunotherapy ( P = .034) and one patient who had high microsatellite instability has survived for 1034 days. Conclusion: CD8 infiltration in tumors and nonsynonymous mutation load might be useful predictive markers for immune checkpoint inhibitors for bladder cancer patients.